If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1a + -1b)(-1a + -1b) = 0 Multiply (-1a + -1b) * (-1a + -1b) (-1a * (-1a + -1b) + -1b * (-1a + -1b)) = 0 ((-1a * -1a + -1b * -1a) + -1b * (-1a + -1b)) = 0 Reorder the terms: ((1ab + 1a2) + -1b * (-1a + -1b)) = 0 ((1ab + 1a2) + -1b * (-1a + -1b)) = 0 (1ab + 1a2 + (-1a * -1b + -1b * -1b)) = 0 (1ab + 1a2 + (1ab + 1b2)) = 0 Reorder the terms: (1ab + 1ab + 1a2 + 1b2) = 0 Combine like terms: 1ab + 1ab = 2ab (2ab + 1a2 + 1b2) = 0 Solving 2ab + 1a2 + 1b2 = 0 Solving for variable 'a'. Factor a trinomial. (a + b)(a + b) = 0Subproblem 1
Set the factor '(a + b)' equal to zero and attempt to solve: Simplifying a + b = 0 Solving a + b = 0 Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. a + b + -1b = 0 + -1b Combine like terms: b + -1b = 0 a + 0 = 0 + -1b a = 0 + -1b Remove the zero: a = -1b Simplifying a = -1bSubproblem 2
Set the factor '(a + b)' equal to zero and attempt to solve: Simplifying a + b = 0 Solving a + b = 0 Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. a + b + -1b = 0 + -1b Combine like terms: b + -1b = 0 a + 0 = 0 + -1b a = 0 + -1b Remove the zero: a = -1b Simplifying a = -1bSolution
a = {-1b, -1b}
| x^2=27x | | (3p+2)(2p+1)= | | 145-4x=23x+22 | | (5a+6a)=51 | | -3+5+2= | | -4+5+3= | | 3x+2[1-3(x-2)]=2x | | 3x(5-x)=1 | | (m+3)(n-4)= | | x^2-3x+xy-3y= | | 7k+5=2k+20 | | -34x+15+15x^2=0 | | 57a^2-21ab-42ac= | | 7x+20=60 | | 6x(12x^2+8x-16)= | | 8s+3-6s=5s+15-9s | | 5q+42=77 | | 9v-42=39 | | 8g-11=5g-2 | | 2pr^2+2prh= | | 5y-1=y+11 | | 5v-27=-2 | | 4r+7=6r-3 | | 3y+2=2y+7 | | 6p-7=71 | | 5x+24=14x-71 | | (a(a^2+a-1)-a^2(a+1))5= | | 7k-6=50 | | 4g+1=2g+9 | | 3(40x-2(5x+8)+10(2-x))= | | 10x+6=-30 | | 3b+4=5b |